Half Iris Matching Based on RED Algorithm - Akeel Ali Al-Hillali; Safaa S Omran (Institute of Advanced Engineering and Science, 2016)
Iris recognition is one of the most accurate identification method and it is powerful for secure of information and identification between users. The Ridge Energy Direction (RED) algorithm is the most accurate and fast approach for iris recognition. The RED algorithm reduces the effects of illumination, since only direction is used. The RED algorithm is applied after a normalization process consisting on two filter types (horizontal and vertical). This paper extends this algorithm by considering the lower portion of the iris because this portion is affected with less noise. We used different size of RED filter on Iris in order to compare the accuracy and time between them. We found that the higher filter size gives more accuracy but more processing time